A-LNT: A Wireless Sensor Network Platform for Low-Power Real-Time Voice Communications. (4th May 2014) - Fu, Yong; Guo, Qiang; Chen, Changying
Abstract : Combining wireless sensor networks and voice communication for multidata hybrid wireless network suggests possible applications in numerous fields. However, voice communication and sensor data transmissions have significant differences, Meanwhile, high-speed massive real-time voice data processing poses challenges for hardware design, protocol design, and especially power management. In this paper, we present a wireless audio sensor network platform A-LNT and study and discuss key elements for systematic design and implementation: node hardware design, low-power voice codec and processing, wireless network topology, hybrid MAC protocol design based on superframe, radio channel allocation, and clock synchronization. Furthermore, we discuss energy management methods such as address filtering and efficient power management in detail. The experimental and simulation results show that A-LNT is a lightweight, low-power, low-speed, and high-performance wireless sensor network platform for multichannel real-time voice communications.